Sustainable Carbon Dots Production from Oil Palm Empty Fruit Bunch for the Photodegradation of Methylene Blue - Wan Ishak, Wan Nuraishah; Tan, Huey Ling; Abu Bakar, Noor Fitrah; Lim, Ying Pei (Journal of Sustainable Materials Processing and Management, 2024)
This paper presents a sustainable approach to produce carbon dots (CDs) using biomass waste as a precursor for the effective photocatalytic degradation of Methylene Blue (MB). CDs were successfully synthesized from Empty Fruit Bunch (EFB) through one-step hydrothermal treatment. The surface morphology, crystal structure, elemental composition analysis, functional groups, and optical absorption of the CDs were determined. Operating parameters influencing the photocatalytic degradation performance, including photocatalyst dosage, pH of MB, and dye concentration were carefully investigated. It has been found that CDs exhibited optimal MB degradation efficiency of 30.23% in 160 minutes using 20 mg/L CDs in a solution containing 10 mg/L of MB at pH 6. A higher pH of MB solution (pH 10) further enhanced the degradation efficiency to 68.5% within 160 minutes. The results showed that the degradation efficiency increases exponentially with time. The kinetic analysis revealed that the photocatalytic reaction followed the pseudo-first order with the highest rate constant of 1.5 x 10-3 min-1. This research demonstrates a simple and sustainable synthetic route for synthesizing CDs by using biomass waste as a natural precursor.